Efektivitas Anthipertensi Calsium Channel Blocker Dibandingkan Angiostensin Reseptor Blocker Pada Pasien Hipertensi Gangguan Ginjal. - Ekanita Desiani; Siti Fatimatul Azahro (LPPM Universitas Abdurrab, 2023)
Hypertension can cause damage to blood vessels in the kidneys so that the kidneys cannot filter blood properly. Appropriate and effective management of hypertension complicated by kidney disorders is needed in patients with kidney disorders to control blood pressure and slow down the occurrence of cardiovascular disease. The use of combination Calcium Channel Blocker antihypertensive drugs compared to combination Angiostensin Receptor Blockers has a therapeutic effect on lowering blood pressure in hypertensive patients with renal impairment. This study aims to determine the effectiveness of the use of antihypertensive Calcium Channel Blockers (CCB) combination compared to Angiotensin Receptor Blocker (ARB) combination in hypertensive patients with renal impairment outpatients at RSUD Kraton Pekalongan. This study is a non-experimental observational study with retrospective data on hypertensive patients with renal impairment from January to December 2022. The samples in this study were medical records of outpatients with hypertension and renal impairment who were given antihypertensive drugs of the CCB and ARB combination groups at the Public Hospital. Kraton that met the patient inclusion criteria. The results showed that the highest percentage of patients were over 60 years of age with 25 people (48%), male sex with 32 people (62%), use of antihypertensive drugs class ARB + diuretics with 16 people (30.7%) and use of antihypertensive group ARB + CCB + diuretic in 16 people (30.7%), the use of combined ARB and CCB drugs resulted in no increase in GFR in 29 people (55.7%) with the result p value = 0.570 p , the effect of drug use The combined ARB and combined CCB resulted in a decrease in blood pressure in 42 people (80.6%) with a p value = 0.178 p. Based on the results of the study, it can be concluded that the most patients are patients aged over 60 years with the sex of male patients, and there is no difference in the effectiveness of using antihypertensive groups CCB and ARB in hypertensive patients with kidney disorders in outpatient care at Kraton Pekalongan Hospital